Analyzing Activity Behavior and Movement in a Naturalistic Environment Using Smart Home Techniques - Cook, Diane J.; Schmitter-Edgecombe, Maureen; Dawadi, Prafulla (IEEE journal of biomedical and health informatics, 2015)
One of the many services that intelligent systems can provide is the ability to analyze the impact of different medical conditions on daily behavior. In this study, we use smart home and wearable sensors to collect data, while (n = 84) older adults perform complex activities of daily living. We analyze the data using machine learning techniques and reveal that differences between healthy older adults and adults with Parkinson disease not only exist in their activity patterns, but that these differences can be automatically recognized. Our machine learning classifiers reach an accuracy of 0.97 with an area under the ROC curve value of 0.97 in distinguishing these groups. Our permutation-based testing confirms that the sensor-based differences between these groups are statistically significant.